If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 10 = 4X + -1(15 + -7x) Reorder the terms: 10 + 7x = 4X + -1(15 + -7x) 10 + 7x = 4X + (15 * -1 + -7x * -1) 10 + 7x = 4X + (-15 + 7x) Reorder the terms: 10 + 7x = -15 + 4X + 7x Add '-7x' to each side of the equation. 10 + 7x + -7x = -15 + 4X + 7x + -7x Combine like terms: 7x + -7x = 0 10 + 0 = -15 + 4X + 7x + -7x 10 = -15 + 4X + 7x + -7x Combine like terms: 7x + -7x = 0 10 = -15 + 4X + 0 10 = -15 + 4X Solving 10 = -15 + 4X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-4X' to each side of the equation. 10 + -4X = -15 + 4X + -4X Combine like terms: 4X + -4X = 0 10 + -4X = -15 + 0 10 + -4X = -15 Add '-10' to each side of the equation. 10 + -10 + -4X = -15 + -10 Combine like terms: 10 + -10 = 0 0 + -4X = -15 + -10 -4X = -15 + -10 Combine like terms: -15 + -10 = -25 -4X = -25 Divide each side by '-4'. X = 6.25 Simplifying X = 6.25
| 5a+3b-6a-8b+2a+6b= | | 4.19+x=19.72 | | 3x-7(8-x)=16 | | one+one= | | 9x+3=12y | | 10-9=81 | | 107-9=81 | | 6c+8-2c=16 | | 16v=12v-4 | | 50x+3=75x-775 | | 7(X+5)+6=-4(-3x+1) | | 50x+3=75x-7.75 | | (6x+8)=(7x-5) | | x(2x-3)+4(x^2+1)= | | 6(1-3m)=3(-4m+6) | | 3(x+10)=8(x) | | x-5=4+7 | | -(15-7x)= | | -8=3b+45 | | 180-74=x | | -2[5w-7]+9=-7 | | -9+22=m-2 | | 5x+14=38-3x | | 6(1-3)=3(-4m+6) | | 3d+3=18-2d | | 529-(8+1)= | | 6(x-2)=3(x) | | 4x+15+2x=6(x+4) | | -5(3-q)+4=5q+11 | | -4(1+7x)-3=7(-6x-3) | | 0.5x-3=0.75x-7.75 | | 5q^4-405=0 |